Policy Implementation During the Covid-19 Pandemic: HIV/AIDS Prevention and Control in Batam City - Nurlaily; Khairina, Etika (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This study aims to describe how the policies in handling and preventing HIV/AIDS by City Batam Government during the Covid-19 Pandemic, which later during the Covid-19 pandemic established several policies aimed at reducing the chain of transmission of the Covid-19 Virus . This research is a descriptive qualitative research. This study used primary data and secondary data. The analysis technique in this study was triangulation which was carried out to check the validity of the data obtained from the results of interviews with informants and the results of interviews with informants. The technique of analyzing data is supported by the N-Vivo 12 Plus application. Policy implementation is seen based on Communication, Resources, Disposition, Bureaucratic Structure. factors influencing policy implementation during the Covid-19 Pandemic were Communication with a value of 15%, Human Resources during the Covid-19 Pandemic with a value of 23%, Disposition 36%, and Bureaucratic Structure with a value of 24%. The research results show that the implementation of policies in achieving policy goals or solving the HIV-AIDS problem during the pandemic has not been fully achieved. based on the characteristics of the problem is not precise. From the point of view of policy-making institutions, HIV and AIDS prevention policies have been made by institutions that are competent in their fields that are in accordance with the character of the policy.